Host species and habitats shape the bacterial community of gut microbiota of three non-human primates: Siamangs, white-handed gibbons, and Bornean orangutans - Ying, Chingwen; Siao, You-Shun; Chen, Wun-Jing; Chen, Yi-Ting; Chen, Szu-Lung; Chen, Yi-Lung; Hsu, Jih-Tay (Frontiers in Microbiology, 2022)
Gut microbiota as the second genomes of hosts, is essential for their hosts to digest food, maintain health, and adapt to environments. The bacterial communities of gut microbiota are influenced by a diverse factors including host physiology and environment. Many non-human primates, being physiologically closest to human, are in danger of extinction. Herein, we analyzed the community structure of the gut microbiota in three non-human primates siamangs (Symphalangus syndactylus, Ss), Bornean orangutans (Pongo pygmaeus, Pp), and white-handed gibbons (Hylobates lar, Hl) housed at the largest Zoo of Taiwan. All Pp and Ss inhabited in Asian tropical rainforest area, while the Hl inhabited in two separate areas, Asian tropical rainforest area and conservation area. Bacterial community diversity of Ss, indicated by Shannon index was significantly higher compared to Hl and Pp, while the richness (Chao 1) and observed operational taxonomic units (OTUs) were similar. Host species was shown to be the dominant factor in shaping the gut microbial community structure. The gut bacterial communities of Hl from conservation area were closely related to each other while the bacterial communities of Hl from rainforest area were dispersedly positioned, as suggested by beta-diversity analysis including Principal Co-ordinates Analysis (PCoA) and Unweighted Pair Group Method with Arithmetic mean (UPGMA). Further analysis revealed significantly higher abundance of Lactobacillus fermentum, L. murinus and an unclassified Lactobacillus species, and lower abundance of Escherichia-Shigella in Hl from conservation area relative to rainforest area. The ratio of Lactobacillus to Escherichia-Shigella was 489.35 and 0.013 in Hl inhabited in conservation and rainforest area, respectively. High abundance of Lactobacillus and Bifidobacterium, and high ratio of Lactobacillus to Escherichia-Shigella was also observed in one siamang that has an impressive longevity of 53 years. The data reveal that host species acted as the fundamental driving factor in modulating the community structure of gut microbiota, but habitats also act as key determinants within species. The presence of high abundance probiotics including Bifidobacterium and Lactobacillus provides potential indicators for future diet and habitat optimization for non-human primates, especially in zoological settings.